Tissue imaging using nonlinear laser scanning microscope - Tay, Kenneth ZiHan (2018)
The importance for a fast and efficient imaging technique is essential today for imaging of biological tissues. From retinal diseases and disorders such as Retinal Vein Occlusion, Diabetic Retinopathy, and Retinal Tear or Detachments to cancer research in the liver, there are sophisticated technologies available today to diagnose these diseases on a macroscopic level, but the optimum parameters aren’t pre-determined prior to the imaging of these biological tissues. A novel technology called two-photon microscopy, which is based on the principle of Confocal Laser Scanning Microscopy and Two-Photon Excitation is being explored for its application in imaging the microstructures of the retina in vivo. This project thus aims to determine the optimal parameters in the imaging of biological tissues using the principles of Confocal Laser Scanning Microscopy to carry out ex-vivo Two-Photon Microscopy. Ultimately obtaining successful images to observe and understand the microstructures of biological tissues such as the retina.